Foundation phase teacher provision by public higher education institutions in South Africa - Whitfield Green (South African Journal of Childhood Education, 2011)
The study reported in this paper investigated foundation phase teacher provision by the public universities in South Africa, with a view to carefully and accurately determine the extent to which foundation phase teacher provision matched national as well as provincial needs. The study draws on data obtained through a survey of teacher provision at the public higher education institutions (HEIs), conducted by the national Department of Education (DoE) in 2009, as well as from data relating to teacher education qualifications and programmes in the Higher Education Management Information System (HEMIS). The study confirmed perceptions that the number of new foundation phase teachers being produced by the public higher education institutions (HEIs) falls short of national and provincial needs, and that the provision of African language foundation phase teachers is particularly problematic, especially in the context of mother-tongue instruction in the early years.